Eating and Sports Habits of University Students in Szeged - Vári, Beáta; Katona, Zoltán; Sajben, Regina; Pálhidai, Anetta; Meszlényi, Emese (Arena-Journal of Physical Activities, 2020)
sity of Szeged conducted an online survey on students studying at different university faculties. The main purpose of the study is to find out how healthconscious today’s students are, what are their eating, fluid consumption and sports habits. Methods. In our descriptive basic research the mode of data collection is structured, largly standardized questionnaire that uses mostly colosed questions and a Likert scale and the survey could be conducted online. The questionnaire was filled in by 746 people, 69.8% were women (521 persons) while 30.2% (225 persons) were men. Results. Their answers gave the following picture: 50% of the students are currently doing sports, most of them do it as a hobby and with friends. As a result of sport activities more than 50% of them changed their eating habits in a positive direction. Nearly 75% of students consider their eating habits healthy. They use different type of diets regularly. The majority eat more times a day and drink acceptable amount of water. The vegetable consumption is higher than fruit intake. Just every tenth students eat fast food every week. Conclusion. For the results mentioned above, it would be important for students to have courses in lifestyle or life coaching, because who do not know the connections between sports and nutrition do not feel their importance either. Implamenting and organizing special programmes would also help to transform a young adult into a conscious and active adult.